Teatralidade, montagem e performance na arte de Ana Maria Pacheco - Martins, Rosilandes Cândida (2016)
Theatricality, Montage and Performance in the Art of Ana Maria Pacheco scrutinizes the visual work of the plastic artist as a main visual body analysis on the series of ten paintings entitled In Illo Tempore I-X (1994), elaborated in the 90 ́s. The approach of this work is that the art of Ana Maria Pacheco (1943) is an intervallic montage of multiple temporalities, and under this perspective, we are headed to assume that the artist reinterprets the cultural-historical universe of her environment of origin and formation relating it dynamically and diversely in her visual work. It also investigates the theatricality inherent in the artist ́s visual work, elaborated through the intervallic and anachronistic montage of the culture, from which a potential performance on images derives to the reception of viewers eyes. The methodology used in this work is a combination of bibliographical research and image analysis starting from the process “constellation and work table” (Didi- Huberman, 2013), which consists in entangling a collection of affinities and relationship between the images themselves. The main concepts approached in this work are the notions of “montage” (Didi-Huberman, 2013), “theatricality” (Féral, 2011), “geopoetics” (Lowenthal, 1982) and “performance and reception” (Zumthor, 2007).